Clustering of Thrombotic Factors with Insulin Resistance in South Asian Patients with Ischaemic Stroke - Kain, Kirti; Catto, Andrew J.; Grant, Peter J. (Thrombosis and Haemostasis, 2002)
We aimed to investigate significant correlations of insulin resistance with thrombotic factors in South Asians with stroke. Correlations of Homeostasis Model Assessment (HOMA)(as a surrogate of insulin resistance) were analysed with 6 thrombotic factors in 140 South Asian patients with a history of confirmed (by computerised tomography) ischaemic stroke. Age and sex adjusted HOMA was correlated to waist-hip ratio (r = 0.38, p = 0.0001), triglycerides (r = 0.22, p = 0.03), systolic blood pressure (r = 0.21, p = 0.04), tissue plasminogen activator (t-PA) (r = 0.22, p = 0.04); plasminogen activator inhibitor 1(PAI-1) (r = 0.26, p = 0.02); fibrinogen (r = 0.25, p = 0.02); and factor VII antigen (r = 0.21, p = 0.06). On regression analysis, with HOMA as dependent variable and significant correlates as independent variables in the model, HOMA was independently associated with PAI-1 antigen. There is extensive clustering of metabolic and thrombotic factors with insulin resistance in South Asian patients with ischaemic stroke, which may contribute to high prevalence of vascular disease in this population.
Keywords: Insulin; stroke; haemostasis; South Asian; ethnic